Applications in basic marketing : clipping from the popular business press - McCarthy, E. Jerome (Edmund Jerome); McCarthy, E. Jerome (Edmund Jerome); Perreault, William D.; McCarthy, E. Jerome (Edmund Jerome).; McCarthy, E. Jerome (Edmund Jerome). (Homewood, Ill. : Irwin, 1991)
'Clippings from the popular business press.'
Includes bibliographical references.
Keywords: Marketing -- Periodicals; Marketing -- Management -- Periodicals